Visual Performance After Bilateral Implantation of a New Enhanced Monofocal Hydrophobic Acrylic Intraocular Lens Targeted for Mini-Monovision - Hugo A. Scarfone; Emilia C. Rodríguez; Jerónimo Riera; Maira Rufiner; Martín Charles (Life)
Background: The aim of this study was to evaluate visual outcomes and patient satisfaction after bilateral implantation of a new hydrophobic acrylic intraocular lens called Clareon (Alcon) using the mini-monovision technique. Methods: A single-center, prospective, nonrandomized study was conducted in Tandil (Buenos Aires, Argentina), including patients scheduled for cataract surgery. To achieve mini-monovision, the spherical equivalent was calculated between −0.25 and +0.25 D for the dominant eye, and between −0.75 and −1.00 D for the non-dominant eye. The main outcomes were uncorrected distance visual acuity (UDVA) and uncorrected intermediate visual acuity (UIVA) evaluated at 66 cm. A secondary outcome, patient satisfaction, was assessed using the CatQuest-9SF questionnaire. Results: The mean binocular UDVA was 0.01 ± 0.05 logMAR three months after surgery, while the mean binocular UIVA was 0.20 ± 0.06 logMAR. The postoperative mean spherical equivalent in the dominant eye was −0.27 ± 0.12, and in the non-dominant eye was −0.87 ± 0.25. Before surgery, the CatQuest-9SF questionnaire revealed that 83.33% of patients were dissatisfied with their vision during daily activities. Over 50% reported significant difficulties with reading newspapers, sewing, and reading TV subtitles. Additionally, 66.6% struggled with recognizing faces, 50% with seeing product prices, and 50% with walking on uneven ground. Post-surgery, most patients experienced improved vision for daily tasks, with no reports of high dissatisfaction or significant difficulties. Patients were quite satisfied with their vision for hobbies and TV subtitles, and very satisfied (90%) with seeing supermarket prices. Conclusions: patients implanted with a new enhanced monofocal IOL using the mini-monovision technique showed improved distance and intermediate visual acuity, reduced need for glasses, and expressed a high degree of satisfaction.